Intoleransi dan Sektarianisme Keagamaan: Sebuah Survey Literatur - Zuly Qodir (Budapest International Research and Critics University, 2017)
The study in this paper provides an explanation about the issue of sectarianism and religious intolerance occurring in Indonesia especially and someother countries. There are several factors that influence such as mentalhealth factors, economic and political factors other than religious commitments that encourage a person to perform jihad actions that are interpretedas